Experimental studies of thermodynamic combustion processes of combustible demonstrators. Issue 1 (1st March 2022) - Iordan, Yu
Abstract: The description of experimental benches for combustion of demonstration elements of material samples - combustion demonstrators (CD) is given. CD for investigating thermodynamic processes during combustion on experimental benches are developed. The results of experimental studies of combustion of CD made of different materials (existing and synthesized) are presented. A new direction of research is formulated - the development of combustible materials and structures made of them, providing the specified characteristics at all stages of operation.